Analisis Pergeseran Struktur Ekonomi dan Sektor Unggulan Di Kabupaten Tabalong Tahun 2013-2017 - Husaini; Siregar, Syahrituah (PPJP ULM, 2019)
This research aims to find out how are the conditions of shifting economic structure andwhich sectors are the leading sectors in Tabalong Regency.This research uses a calculating change in the value of sectoral contributions to GDPformation, location quotient, dynamic location quotient, and classic shift share. By usingsecondary data in the form of GDP according to employment at constant prices.The study results indicate a shift in the economic structure in Tabalong Regency, namelythe traditional sector (primary) to the modern industry (tertiary and secondary). And when themining and quarrying sector's contribution is calculated, there are five leading sectors inTabalong Regency. The industry is processing, construction, providing accommodation andeating, industrial real estate, and other services. But when the mining and quarrying sectorcontribution was eliminated, there were only two superior Tabalong Regency sectors. The sectorincludes construction and provision of accommodation and food for drinking. It is known basedon the prime criteria of LQ, DLQ, industrial mix (PS), and competitive advantage (DS), whichhave the highest value among several sectors.